On one solution of a periodic boundary value problem for a hyperbolic equations - Tokmagambetova, T.D.; Orumbayeva, N.T. (Bulletin of the Karaganda University. Mathematics series., 2023)
In a rectangular domain, we consider a boundary value problem periodic in one variable for a system of partial differential equations of hyperbolic type. Introducing a new unknown function, this problem is reduced to an equivalent boundary value problem for an ordinary differential equation with an integral condition. Based on the parametrization method, new approaches to finding an approximate solution to an equivalent problem are proposed and its convergence is proved. This made it possible to establish conditions for the existence of a unique solution of a semiperiodic boundary value problem for a system of second-order hyperbolic equations.
Keywords: boundary value problem; hyperbolic equations; algorithm; parametrization method; approximate solution